Diplomatic protocol as a tool of international economic relations - Pshtyka Vadim (Baltic Region, 2011)
Both the official (state and diplomatic) and business protocols are frequently used in Europe; in Russia, it has become a focus of attention in recent years. Thus, there arises a need of training specialists in protocol. However, this aspect has not been tackled effectively by Russian universities. This article is aimed at identifying the need for the professional study of protocol at Russian universities. The paper analyses the level of teaching protocol disciplines in Europe and Russia and considers the results of the first Russian forum on protocol. The main conclusion drawn is that there is a need for introducing a qualification of an expert in protocol into Russian science. This research will help Russian universities create training plans for protocol disciplines.